2014
DOI: 10.1111/bjet.12203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of degree of segmentation and learner disposition on multimedia learning

Abstract: The construction of asynchronous learning environments often involves the creation of self‐paced multimedia instructional episodes that provide the learner with control over the pacing of instruction (segmentation); however, does the amount of segmentation impact learning? This study explored the effects of the degree of segmentation on recall and application of new knowledge and the nature of learner dispositions toward segmentation. Undergraduate students (n = 212) were randomly assigned to engage in a 9‐min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 31 publications
2
36
1
2
Order By: Relevance
“…Most previous studies used videos roughly 2 minutes long and had anywhere from 6 to 16 segments (Khacharem et al ., 2013; Mayer & Chandler, 2001; Spanjers et al ., 2012; Spanjers, Wouters, Van Gog, & Van Merriënboer, 2011). A few studies have gone beyond 2 minutes in length, but still generally are 9 minutes or less (Biard, Cojean, & Jamet, 2018; Doolittle, Bryant, & Chittum, 2015; Hasler et al ., 2007). Only two longer studies were found, including one that was 15 minutes (Moreno, 2007) and another that was an hour long (Fong et al ., 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Most previous studies used videos roughly 2 minutes long and had anywhere from 6 to 16 segments (Khacharem et al ., 2013; Mayer & Chandler, 2001; Spanjers et al ., 2012; Spanjers, Wouters, Van Gog, & Van Merriënboer, 2011). A few studies have gone beyond 2 minutes in length, but still generally are 9 minutes or less (Biard, Cojean, & Jamet, 2018; Doolittle, Bryant, & Chittum, 2015; Hasler et al ., 2007). Only two longer studies were found, including one that was 15 minutes (Moreno, 2007) and another that was an hour long (Fong et al ., 2012).…”
Section: Methodsmentioning
confidence: 99%
“…This text density was chosen because it corresponds to approximately one concept per slide. Research on segmenting (delivering content in segments) indicates that smaller segments tend to result in better recall (Doolittle, Bryant, & Chittum, 2015). Illustrations or photographs were included in some slides to support the slide’s dominant concept when appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…Multimedia offers a kind of effective learning environment by combining a variety of formats such as text, pictures, animations, audio, and videos (Doolittle, Bryant, & Chittum, ). A multimedia learning environment can present relevant materials in various formats and help students process the materials in meaningful ways, for example, by integrating learning materials with relevant prior concepts, and organizing them into a consistent and coherent cognitive structure.…”
Section: Literature Reviewmentioning
confidence: 99%